DETERMINING PRE-ERUPTIVE COMPOSITIONS OF LATE PALEOZOIC MAGMA FROM KAOLINIZED VOLCANIC ASHES: ANALYSIS OF GLASS INCLUSIONS IN QUARTZ MICROPHENOCRYSTS FROM TONSTEINS - Webster J.D.; Congdon R.D.; Lyons P.C. (My University, 1995)
Glass inclusions in quartz microphenocrysts were analyzed for major and minor elements by electron microprobe and H, Li, Be, B, Rb, Sr, Y, Nb, Mo, Sn, Cs, Ce, Th, and U by ion microprobe. The phenocrysts and inclusions occur as fresh relicts in about eleven strongly kaolinized, air-fall volcanic ash units (tonsteins) that outcrop in five states located in the central Appalachian basin; the ashes were erupted during the Pennsylvanian. Even though the whole-rock tonstein samples are extremely altered, the glass trapped in quartz microphenocrysts preserves pre-eruptive melt compositions, and, consequently, the inclusions are useful for determining compositions of source magmas and identifying geochemical trends indicative of magmatic evolution.Interpretation of inclusion compositions indicates the strongly altered tonsteins were derived from potassium-enriched, metaluminous to mildly peraluminous magma(s). The tonsteins can be divided into two groups on the basis of trapped melt compositions: older tonsteins that have inclusions with high Sr and normative quartz contents and comparatively low concentrations of U, Th, Rb, Y, Cs, Nb, F, and Cl (+/-Be) and younger tonsteins whose inclusions contain low Sr and normative quartz and high concentrations of U, Th, Rb, Y, Cs, Nb, F, and Cl (+/-Be). In general, as concentrations of Sr decreased, the magmatic abundances of Rb, Y, Cs, Nb, U, Th, Cl, and F (+/-Be) increased. The associated magma or magmas were highly evolved, volatile enriched, and contained Rb, Nb, and Y abundances characteristic of continental within-plate granites; compositions ranged from high-silica rhyolite to topaz rhyolite.Pre-eruptive volatile abundances in the source magma(s) were generally high but also highly variable. Chlorine contents of melt(s) ranged from 0.02-0.23 wt%, and F ranged from 0.01-0.7 wt%. Concentrations of H2O in melt(s) ranged from 1.6-6.5 wt%. The high pre-eruptive H2O contents are consistent with large eruptive volumes indicating the precursor rhyolites, which weathered to tonsteins, were a result of plinian eruptions. Even though pre-eruptive water concentrations exhibit no recognizable trends with any elements studied, magmatic evolution appears to have been a strong function of F and H2O in melt(s); the thermal stabilities of quartz and feldspar were controlled by F and H2O activities at pressures of approximately 0.5-1 kbar.
Keywords: Paleozoic; Paleozoic; Палеозой